Aging, factor returns, and immigration policy - Lena Calahorrano; Jens Oliver Lorz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
In this note we analyze how aging affects immigration policy. We set up a dynamic political-economy model of representative democracy in which the government of the destination country sets the immigration level to maximize aggregate welfare of the constituency. Aging, i.e. a decline in the growth rate of the native population, has an expansionary effect on immigration. This immigration effect may even overcompensate the initial decline in population growth such that the total labor force grows more strongly and the capital stock per worker declines. We also compare our results to the social planner allocation and to the median-voter equilibrium.
Keywords: D78; F22; 330; Demographic change; political economy; immigration policy